Preliminary germination trials in Puya raimondii Harms (BROMELIACEAE) - Suni, Mery L. (2001)
Puya raimondii Harms is an endemic especie of the highlands of Peru and Bolivia, whose population and area of distribution are being reduced. Aiming at contributing to the knowledge of the mechanisms of propagation of this species, a study of the effects of the illumination and stratification on the germination of the seed was carried out. The seed was collected in the rodal of Puya raimondii in Huashta Cruz (Pueblo Libre, Ancash) in December 1999 and were stored under laboratory conditions in Lima until the tests. The seeds were desinfected with sodium hipochloride 2,6% and for the germination test seeds were placed in petri dishes with distilled and sterilized water during 2000. The preliminary results show that the seed of Puya raimondii has a high percentage and velocity of germination when exposed to light. A similar effect was achieved by stratifying them for two months at 11 °C or by increasing time of storage to 8 months, but germination dropped upon applying both processes simultaneously. We hypothesize that the high seed moisture content and high temperature during storage and germination affect germination success negatively.